HcpR of Porphyromonas gingivalis Is Required for Growth under Nitrosative Stress and Survival within Host Cells - Lewis, Janina P. (American Society for Microbiology, 2012)
Although the Gram-negative, anaerobic periodontopathogen Porphyromonas gingivalis must withstand nitrosative stress, which is particularly high in the oral cavity, the mechanisms allowing for protection against such stress are not known in this organism. In this study, microarray analysis of P. gingivalis transcriptional response to nitrite and nitric oxide showed drastic upregulation of the PG0893 gene coding for hybrid cluster protein (Hcp), which is a putative hydroxylamine reductase. Although regulation of hcp has been shown to be OxyR dependent in Escherichia coli, here we show that in P. gingivalis its expression is dependent on the Fnr-like regulator designated HcpR. Growth of the isogenic mutant V2807, containing an ermF-ermAM insertion within the hcpR (PG1053) gene, was significantly reduced in the presence of nitrite (P < 0.002) and nitric oxide-generating nitrosoglutathione (GSNO) (P < 0.001), compared to that of the wild-type W83 strain. Furthermore, the upregulation of PG0893 (hcp) was abrogated in V2807 exposed to nitrosative stress. In addition, recombinant HcpR bound DNA containing the hcp promoter sequence, and the binding was hemin dependent. Finally, V2807 was not able to survive with host cells, demonstrating that HcpR plays an important role in P. gingivalis virulence. This work gives insight into the molecular mechanisms of protection against nitrosative stress in P. gingivalis and shows that the regulatory mechanisms differ from those in E. coli.